Comparison of the physical fitness of karate and taekwondo elite athletes - Gunawan, G. (Journal of Education, Health and Sport, 2021)
Introduction. A coach compiles and determines a training program based on the physical fitness profile of the athlete. Central Sulawesi taekwondo and karate athletes have been undergoing independent training since mid-2020.